A novel secret key generation based on image link - Sulaiman, Alyaa Ghanim; Taha Alshaikhli, Imad Fakhri; Wahiddin, Mohamed Ridza; Houri, S; Jamil, Norziana; Ismail, Ahmad Fadzil (Science Publishing Corporation Inc, 2018)
One of the main problems with symmetric encryption is key distribution especially when involving large number of users i.e to generate identical keys at different locations. To address this challenge, we proposed a novel algorithm of secret key infusion protocol (SKIP) to generate an identical secret key. While, the key is generated based on a provided image link, starting pattern and string length which must be kept in secret as the algorithm is publicly known. The image from website must be a static image and used as the input of random bits to produce string of hexadecimal values. In a case where image link is compromised, the adversary has to guess other layers of parameters in starting pattern and string length. The generated secret keys were identical at two different locations. In other observation, different secret keys were generated even with the same image link and pattern length but different starting pattern.